Needles in the blue sea: Sub-species specificity in targeted protein biomarker analyses within the vast oceanic microbial metaproteome - Saito, Mak A.; Dorsk, Alexander; Post, Anton F.; McIlvin, Matthew R.; Rappé, Michael S.; DiTullio, Giacomo R.; Moran, Dawn M. (Proteomics (Weinheim), 2015)
Proteomics has great potential for studies of marine microbial biogeochemistry, yet high microbial diversity in many locales presents us with unique challenges. We addressed this challenge with a targeted metaproteomics workflow for NtcA and P‐II, two nitrogen regulatory proteins, and demonstrated its application for cyanobacterial taxa within microbial samples from the Central Pacific Ocean. Using METATRYP, an open‐source Python toolkit, we examined the number of shared (redundant) tryptic peptides in representative marine microbes, with the number of tryptic peptides shared between different species typically being 1% or less. The related cyanobacteria Prochlorococcus and Synechococcus shared an average of 4.8 ± 1.9% of their tryptic peptides, while shared intraspecies peptides were higher, 13 ± 15% shared peptides between 12 Prochlorococcus genomes. An NtcA peptide was found to target multiple cyanobacteria species, whereas a P‐II peptide showed specificity to the high‐light Prochlorococcus ecotype. Distributions of NtcA and P‐II in the Central Pacific Ocean were similar except at the Equator likely due to differential nitrogen stress responses between Prochlorococcus and Synechococcus. The number of unique tryptic peptides coded for within three combined oceanic microbial metagenomes was estimated to be ∼4 × 107, 1000‐fold larger than an individual microbial proteome and 27‐fold larger than the human proteome, yet still 20 orders of magnitude lower than the peptide diversity possible in all protein space, implying that peptide mapping algorithms should be able to withstand the added level of complexity in metaproteomic samples.